Impacts of Microplastics, Cadmium, and Their Mixtures on Biochemical Biomarkers in the Freshwater Bivalve Corbicula fluminea (Bivalvia, Corbiculidea) - Susana Parra; Dércia Santos; Ana Luzio; Edna Cabecinha; Maria José Saavedra; Jesús Gago; Simone Varandas; Sandra Mariza Monteiro (Diversity)
Microplastics (MPs) are a worldwide contaminant of significant environmental concern due to their persistence, widespread distribution, and toxic potential. These plastic particles are taken up by invertebrates such as bivalves. Previous studies have indicated that MPs can serve as carriers for other contaminants, such as heavy metals, thereby increasing their bioavailability to organisms, with unpredictable ecological consequences. Therefore, the main aim of this study was to evaluate the effects of exposure to MPs, cadmium (Cd), and their mixtures (Mix) in the gills, digestive gland, and gonad of the Asian clam, Corbicula fluminea, assessing the oxidative stress responses, LDH activity, and neurotoxicity over 7, 14, 21, and 30 days. The results show that exposure to MPs and their mixtures with the lowest Cd concentration led to the activation of the first line of antioxidant defenses, especially SOD and CAT, in the gills, digestive gland, and gonads. An increase in GST activity was also observed in the gonads. However, the response of GST activity in the gills and digestive gland was opposite that observed in the gonads. Furthermore, LDH activity exhibited contrasting responses, increasing in the digestive gland and decreasing in the gills and gonads. Exposure to MPs induced AChE activity, which contradicts previous findings. The results provide novel insights into the biological responses occurring in different target organs and shed light on the effects of MPs and their mixtures on C. fluminea.